IMF Staff papers, Volume 41 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1994)
This paper examines effects of economic growth and speed of adjustment on openness, human development, and fiscal policies. The model developed in this paper postulates that learning through experience raises labor productivity with three major consequences. First, the steady-state growth rate of output becomes endogenous and is influenced by government policies. Second, the speed of adjustment to steady-state growth increases and enhanced learning further reduces adjustment time. Third, both steady-state growth and the optimal net rate of return to capital are higher than the sum of the exogenous rates of technical change and population growth.